Comparative metabolism and tolerability of racemic primaquine and its enantiomers in human volunteers during 7-day administration - Khan, Washim; Wang, Yan-Hong; Chaurasiya, Narayan D.; Nanayakkara, N. P. Dhammika; Bandara Herath, H. M.; Harrison, Kerri A.; Dale, Gray; Stanford, Donald A.; Dahl, Eric P.; McChesney, James D.; Gul, Waseem; ElSohly, Mahmoud A.; et al. (Frontiers in Pharmacology, 2023)
Primaquine (PQ) is an 8-aminoquinoline antimalarial, active against dormant Plasmodium vivax hypnozoites and P. falciparum mature gametocytes. PQ is currently used for P. vivax radical cure and prevention of malaria transmission. PQ is a racemic drug and since the metabolism and pharmacology of PQ’s enantiomers have been shown to be divergent, the objectives of this study were to evaluate the comparative tolerability and metabolism of PQ with respect to its two enantiomers in human volunteers in a seven days’ treatment schedule. Fifteen subjects with normal glucose-6-phosphate dehydrogenase (G6PDn) completed four arms, receiving each of the treatments, once daily for seven days, in a crossover fashion, with a 7-14 day washout period in between: R-(-) enantiomer (RPQ) 22.5 mg; S-(+) enantiomer (SPQ) 22.5 mg; racemic PQ (RSPQ) 45 mg, and placebo. Volunteers were monitored for any adverse events (AEs) during the study period. PQ and metabolites were quantified in plasma and red blood cells (RBCs) by UHPLC-UV-MS/MS. Plasma PQ was significantly higher in SPQ treatment group than for RPQ. Carboxy-primaquine, a major plasma metabolite, was much higher in the RPQ treated group than SPQ; primaquine carbamoyl glucuronide, another major plasma metabolite, was derived only from SPQ. The ortho-quinone metabolites were also detected and showed differences for the two enantiomers in a similar pattern to the parent drugs. Both enantiomers and racemic PQ were well tolerated in G6PDn subjects with the 7-day regimen; three subjects showed mild AEs which did not require any intervention or discontinuation of the drug. The most consistent changes in G6PDn subjects were a gradual increase in methemoglobin and bilirubin, but these were not clinically important. However, the bilirubin increase suggests mild progressive damage to a small fraction of red cells. PQ enantiomers were also individually administered to two G6PD deficient subjects (G6PDd), one heterozygous female and one hemizygous male. These G6PDd showed similar results with the two enantiomers, but the responses in the hemizygous male were more pronounced. These studies suggest that although the metabolism profiles of individual PQ enantiomers are markedly different, they did not show significant differences in the safety and tolerability in G6PDn subjects.